Tale of a Butcher Shop - Hanabusa, Aya (Japan, 2013)
In Kaizuka city, Osaka, a family of butchers raises cows, slaughters them and sells the meat. They face discrimination but devote themselves completely to the lives of the cows in their family business. This documentary sheds light on human beings as living creatures and explores the essence of life.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films